Genetic variability analyses for yield and physiological traits in groundnut (Arachis hypogaea L.) genotypes: Genetic variability analyses for yield and physiological traits in groundnut - NARENDRA KUMAR,; B C AJAY,; A L RATHANAKUMAR,; T RADHAKRISHNAN,; K S JADON,; B M CHIKAN, (Journal of Oilseeds Research, 2019)
Twenty different groundnut genotypes were evaluated in a randomized block design with three replications during kharif 2012 to study the variability parameters, heritability, genetic advance, correlation coefficient and path analysis for ten characters. Analysis of variance revealed highly significant differences among genotypes for all the traits except stability of soil plant analytical development (SPAD) and Chlorophyll Meter Reading 45 days after sowing indicating that adequate variability was found in the genotypes studied for most of the characters. The characters like 100 kernel weight, SPAD Chlorophyll Meter Reading 75 days after sowing, specific leaf area 75 days after sowing and rust resistance had high heritability with high genetic advance as per cent of mean and medium genotypic coefficient of variation indicating greater role of additive gene effects on these traits. While pod yield had moderate genotypic coefficient of variation and heritability along with high genetic advance as per cent of mean revealed that this character is also governed by additive gene effects and selection would be effective even in the early generation. Days to maturity, shelling outturn and specific leaf area 45 days after sowing had moderate heritability accompanied with low genotypic coefficient of variation and genetic advance indicating these traits are governed by non-additive gene effects. Selection may be practiced in later generations for improving these traits. The results on genotypic correlation coefficients revealed that pod yield had significant highly positive correlation with days to maturity, 100-kernel weight, and SPAD Chlorophyll Meter Reading 45 days after sowing while it was negative and significant for days to flower initiation and rust disease. SPAD Chlorophyll Meter Reading 45 days after sowing and SPAD Chlorophyll Meter Reading 75 days after sowing had highly significant negative correlation with specific leaf area 45 days after sowing and specific leaf area 75 days after sowing. Specific leaf area 45 days after sowing had highly significant negative correlation with rust. Therefore, SPAD Chlorophyll Meter Reading value could be used to identify genotypes with low specific leaf area and rust resistance. Path analysis indicated that 100-kernel weight had high positive direct effect with highly significant positive correlation with pod yield. Hence, this character may be effective for selection of high pod yield.